The Effects of Problem-Based Learning on Critical Thinking Skills and Student Science Literacy - Suhirman Suhirman; Husnul Khotimah (Universitas Pendidikan Mandalika, 2020)
This study aimed to describe the effect of problem-based learning on students' critical thinking skills and scientific literacy. This research is a quasi-experimental study with pre-test-post test control group design. Sampling was done by saturated sampling technique in which the experimental class consisted of 35 students and the control class was 34 students. Data on critical thinking skills and student scientific literacy were collected using test instruments which were then analyzed descriptively and statistically. The results showed that the Problem-based Learning model had more effect on students’ critical thinking and scientific literacy (p <0.05) than conventional learning models applied to the control class. Based on the results of the study, it can be concluded that the Problem-based Learning model significantly effect on students’ critical thinking and science literacy in class XI MAN 1 Mataram.